2008
DOI: 10.3899/jrheum.080356
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Dickkopf-1 and Radiological Progression in Patients with Early Rheumatoid Arthritis Treated with Etanercept

Abstract: Dkk-1 may be an important mediator of bone erosion in patients with RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
35
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 12 publications
8
35
2
3
Order By: Relevance
“…Combining both techniques, 26 cases of erosive arthritis (86.7%) were detected. These results are consistent with Wakefield et al, and Brentano et al their study showed that in 40 RA patients US performed on the MCP joints of the dominant hand, detected 6.5-fold more joints with erosions than that detected with X-rays .On other hand, X-rays detected erosion in another 10 (8.8%) patients not detected by US, so combined both techniques revealed 52 (45.6%) patients with erosive diseases [28,29]. So if performing US on a limited number of joints, this reduces the time for examination, it also decreases the capacity to detect erosions.…”
Section: Discussionsupporting
confidence: 89%
“…Combining both techniques, 26 cases of erosive arthritis (86.7%) were detected. These results are consistent with Wakefield et al, and Brentano et al their study showed that in 40 RA patients US performed on the MCP joints of the dominant hand, detected 6.5-fold more joints with erosions than that detected with X-rays .On other hand, X-rays detected erosion in another 10 (8.8%) patients not detected by US, so combined both techniques revealed 52 (45.6%) patients with erosive diseases [28,29]. So if performing US on a limited number of joints, this reduces the time for examination, it also decreases the capacity to detect erosions.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, DKK-1 levels are associated with an increase in the number of articular erosions independently of age, baseline radiological features, C-reactive protein, or disease activity. 33 Systemic bone loss has been correlated with inflammation as well with aging and other inflammatory diseases; the mechanisms are very similar to the ones demonstrated in RA. 1 Figure 1 summarizes the role of T cells in the regulation of osteoclastogenesis in RA.…”
Section: Inflammatory Diseases Immune System and Bonementioning
confidence: 58%
“…Moreover, Dkk-1 expression has been reported to be positively correlated with bone mineral density in bone biopsy specimens of postmenopausal women and also with bone loss in arthritic patients (33,34). Thus, the contribution of Dkk-1 to bone biology in humans remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%